Discovery of Potential Natural Dipeptidyl Peptidase-4 Inhibitors for Type-2 Diabetes Treatment via Structure-Based Virtual Screening - Sara Ranjbar; Mehrane Mohammadabadi Kamarei; Amirhossein Sakhteman; Mehdi khoshneviszadeh (Shiraz University of Medical Sciences, 2019)
Dipeptidyl peptidase IV (DPP-4) is a serine protease that plays a crucial role in glucose metabolism; hence, it is a significant target for type II diabetes mellitus treatment. DPP-4 inhibitors decrease glucose concentrations in such patients by preventing the rapid degradation and thereby lengthening the physiological actions of hypoglycemic incretin hormones. In this study, a structure-based virtual screening strategy was applied to search for novel natural DPP4 inhibitors. From the Supernatural database, 1856 natural structures were picked up and were subjected to molecular docking analysis. Thirteen of them were identified to form more stable complexes than the co-crystallized ligand with the DPP-4 protein. The drug-likeness and pharmacokinetic properties of the top five compounds were also predicted. It was proved that the compounds were compliant with the drug-likeness rules and possess favorable pharmacokinetic properties. The proposed natural compounds can be introduced as potential DPP-4 inhibitors that might be promising leads for further drug development.